Digitalization as the basis of the EU economic policy in creating a single international digital market - Mekhovych, Serhii; Poliakova, Tetiana; Kuzmynskyi, Kostiantyn (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article deals with topical issues related to the creation of a single international digital market. The conditions in which Ukraine's industrial complex will have to operate in the near future are influenced by globalization. The European Union (EU) actively supports and develops the digital economy as a basis for the development of all sectors of the regional economy. The EU's economic policy promotes the digitalization of societies in the EU member states and aims to facilitate the development of a single digital market and the eventual creation of the EU Digital Union. The creation of a single digital market is one of the main prospects and challenges for the European Union. Digitalization has created a world without borders, and its implementation requires a new form of governance based on its specific characteristics. This process requires addressing a number of practical and political issues in the economic and trade relations of the international community.The most influential factors in these processes are digital transformation, the pandemic, and military conflicts. The article provides brief information on the essence of these processes.

У статті розглядаються актуальні питання щодо створення єдиного міжнародного цифрового ринку. На умови, в яких найближчим часом доведеться працювати промисловому комплексу України, впливає глобалізація. Європейський Союз (ЄС) активно підтримує та розвиває цифрову економіку як основу для розвитку всіх секторів регіональної економіки. Економічна політика ЄС сприяє цифровізації суспільств у державах-членах ЄС і спрямована на сприяння розвитку єдиного цифрового ринку та остаточному створенні Цифрового союзу ЄС. Створення єдиного цифрового ринку є однією з головних перспектив і викликів для Європейського Союзу. Цифровізація створила світ без кордонів, і її реалізація вимагає нової форми управління, заснованої на його специфічних характеристиках. Цей процес вимагає вирішення низки практичних і політичних питань в економічних і торговельних відносинах міжнародної спільноти. Найвпливовішими чинниками цих процесів є цифрова трансформація, пандемія та військові конфлікти. У статті подано короткі відомості про сутність цих процесів.
Цифровізація як основа економічної політики ЄС у створенні єдиного міжнародного цифрового ринку
Keywords: economic policy; globalization; digitalization; digital transformation; single digital market; European Union; економічна політика; глобалізація; цифровізація; цифрова трансформація; єдиний цифровий ринок; Європейський Союз